Find the information you're looking for at Westonci.ca, the trusted Q&A platform with a community of knowledgeable experts. Experience the ease of finding quick and accurate answers to your questions from professionals on our platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
To solve the expression [tex]\((a + 3b)^3\)[/tex], we need to expand it completely. Here is the step-by-step process:
1. Use the binomial theorem:
The binomial theorem states that [tex]\((x + y)^n\)[/tex] can be expanded as the sum of the terms of the form [tex]\(\binom{n}{k} x^{n-k} y^k\)[/tex], where [tex]\(\binom{n}{k}\)[/tex] is a binomial coefficient and [tex]\(k\)[/tex] ranges from 0 to [tex]\(n\)[/tex].
2. Apply the binomial theorem for [tex]\( (a + 3b)^3 \)[/tex]:
In our case, [tex]\(x = a\)[/tex], [tex]\(y = 3b\)[/tex], and [tex]\(n = 3\)[/tex].
[tex]\[(a + 3b)^3 = \sum_{k=0}^{3} \binom{3}{k} a^{3-k} (3b)^k\][/tex]
3. Calculate each term individually:
- When [tex]\(k = 0\)[/tex]:
[tex]\[ \binom{3}{0} a^{3-0} (3b)^0 = 1 \cdot a^3 \cdot 1 = a^3 \][/tex]
- When [tex]\(k = 1\)[/tex]:
[tex]\[ \binom{3}{1} a^{3-1} (3b)^1 = 3 \cdot a^2 \cdot 3b = 9a^2b \][/tex]
- When [tex]\(k = 2\)[/tex]:
[tex]\[ \binom{3}{2} a^{3-2} (3b)^2 = 3 \cdot a \cdot (3b)^2 = 3 \cdot a \cdot 9b^2 = 27ab^2 \][/tex]
- When [tex]\(k = 3\)[/tex]:
[tex]\[ \binom{3}{3} a^{3-3} (3b)^3 = 1 \cdot 1 \cdot (3b)^3 = (3b)^3 = 27b^3 \][/tex]
4. Combine all the terms:
[tex]\[ (a + 3b)^3 = a^3 + 9a^2b + 27ab^2 + 27b^3 \][/tex]
So the expanded form of [tex]\((a + 3b)^3\)[/tex] is:
[tex]\[ a^3 + 9a^2b + 27ab^2 + 27b^3 \][/tex]
1. Use the binomial theorem:
The binomial theorem states that [tex]\((x + y)^n\)[/tex] can be expanded as the sum of the terms of the form [tex]\(\binom{n}{k} x^{n-k} y^k\)[/tex], where [tex]\(\binom{n}{k}\)[/tex] is a binomial coefficient and [tex]\(k\)[/tex] ranges from 0 to [tex]\(n\)[/tex].
2. Apply the binomial theorem for [tex]\( (a + 3b)^3 \)[/tex]:
In our case, [tex]\(x = a\)[/tex], [tex]\(y = 3b\)[/tex], and [tex]\(n = 3\)[/tex].
[tex]\[(a + 3b)^3 = \sum_{k=0}^{3} \binom{3}{k} a^{3-k} (3b)^k\][/tex]
3. Calculate each term individually:
- When [tex]\(k = 0\)[/tex]:
[tex]\[ \binom{3}{0} a^{3-0} (3b)^0 = 1 \cdot a^3 \cdot 1 = a^3 \][/tex]
- When [tex]\(k = 1\)[/tex]:
[tex]\[ \binom{3}{1} a^{3-1} (3b)^1 = 3 \cdot a^2 \cdot 3b = 9a^2b \][/tex]
- When [tex]\(k = 2\)[/tex]:
[tex]\[ \binom{3}{2} a^{3-2} (3b)^2 = 3 \cdot a \cdot (3b)^2 = 3 \cdot a \cdot 9b^2 = 27ab^2 \][/tex]
- When [tex]\(k = 3\)[/tex]:
[tex]\[ \binom{3}{3} a^{3-3} (3b)^3 = 1 \cdot 1 \cdot (3b)^3 = (3b)^3 = 27b^3 \][/tex]
4. Combine all the terms:
[tex]\[ (a + 3b)^3 = a^3 + 9a^2b + 27ab^2 + 27b^3 \][/tex]
So the expanded form of [tex]\((a + 3b)^3\)[/tex] is:
[tex]\[ a^3 + 9a^2b + 27ab^2 + 27b^3 \][/tex]
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.